2021
DOI: 10.1038/s41598-021-83671-6
|View full text |Cite
|
Sign up to set email alerts
|

Seepage field characteristic and stability analysis of tailings dam under action of chemical solution

Abstract: As one of the important influencing factors of tailings dam stability, seepage field distribution within the dam is often affected by the tailings mineral characteristics. While the alkalinity or acidity of reservoir water and long term immersion will partially change the physical and mechanical properties of tailings. This study carried out permeability tests of tailings under the action of chemical solution. On this basis, a three dimensional (3D) model was constructed to analyze the velocity field and effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Yang et al ( 2022) presented that the tailing dam was stable and safe under normal water level and rainfall conditions, but the stability and safety of the dam decreased significantly under high water level and rainfall conditions, and the risk of seepage failure increased. [6] Zhang et al ( 2021) concluded that the permeability coefficient ratio is an important parameter for the seepage stability analysis of tailings dam, which should be determined by the field test and adjusted according to the actual situation. [7] Fetisov et al ( 2020) believed that seepage evaluation should be carried out when designing of dams' height increase in a framework of water balance prediction.…”
Section: Problem Definitionmentioning
confidence: 99%
“…Yang et al ( 2022) presented that the tailing dam was stable and safe under normal water level and rainfall conditions, but the stability and safety of the dam decreased significantly under high water level and rainfall conditions, and the risk of seepage failure increased. [6] Zhang et al ( 2021) concluded that the permeability coefficient ratio is an important parameter for the seepage stability analysis of tailings dam, which should be determined by the field test and adjusted according to the actual situation. [7] Fetisov et al ( 2020) believed that seepage evaluation should be carried out when designing of dams' height increase in a framework of water balance prediction.…”
Section: Problem Definitionmentioning
confidence: 99%
“…The study of blockiness level is of great significance to avoid geological disasters such as rockfalls and tailings pond failures (Wang et al, 2019;Wang et al, 2021;Wang et al, 2022a;Lin et al, 2022;Ma and Liu, 2022). Blockiness is defined as the percentage of the volume of isolated blocks formed by fractures to the total volume of the rock (Xia et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The statistical analysis of many tailings pond accidents reveals many reasons for tailings pond accidents, including rainstorms, overtopping, earthquake liquefaction, seepage failure, dam foundation instability, dam structure failure, and load increase. The final cause of dam instability, which mainly refers to changes in the stress fields and seepage fields of tailings dams caused by the aforementioned factors (Wang et al, 2021), is discussed. It is worth noting that the instability characteristics of tailings ponds are completely different at high stress and low stress, so it is necessary to study them.…”
Section: Introductionmentioning
confidence: 99%